Spiritual Intelligence as a predictor of mental health problems among high school students - Shabani, Jafar; Hassan, Siti Aishah (Wiley-Blackwell Publishing, 2014)
This study investigated the relationship between Spiritual Intelligence (SI) and mental health problem scale and sub-scales (somatic symptoms, anxiety, social dysfunction and depression) among high school students. The participants in the study were students of 10th, 11th, and 12th grades from 8 public schools in Gorgan City which is located in the northern of Iran. They were 247 high school students, specifically comprised 124 boys and 123 girls, with age ranging between 15– 17 years old. The research is quantitative in nature –correlation– and tested for the alternative hypotheses. Three valid and reliable instruments were used to assess the participants’ SI, and mental health problems scale and sub-scales. Data analysis included frequencies, percentages, mean scores, Pearson’s correlation and multiple regression analysis. The findings of this study supported the hypothesis that there were negative relationships between SI, and scale and sub-scales of mental health problems. The findings of this study indicate that students with high SI have Low mental health problem scale and sub-scales (somatic symptoms, anxiety, social dysfunction and depression). It was also found that the SI sub-scales are significant predictors for mental health problem scale and sub-scales.